Is Jacques Derrida a Transcendental Philosopher? Three Interpretations - Baranova, Jūratė (Problemos, 2001)
The article aims to discuss different problematic strategies discernible in the contemporary tradition of interpretation of Jacques Derrida’s texts. The article starts with the problem of the possibility for a “living” philosopher to expect to be interpreted according to the line he is suggesting himself. In his Letter to Japaneese Friend Derrida discusses the limits of deconstruction showing the impossibility of define what deconstruction is. Nevertheless, one can discern different interpretative strategies, defining what deconstruction “is”. This article criticises three of them, depicting this discussion as a Weberian clash of incommensurable values; as an example of lasting discussion between Kantians and anti-Kantians. In this discussion, neo-Kantian Jürgen Habermas interprets Derrida as a follower of Nietzsche’s line and criticises him for preferring rhetoric instead of logic which is the main structuring modus of philosophical text. Gasche and Norris suggest a different possibility of interpretation. They see Derrida as slightly Kantian, writing in the line of the tradition of epistemological critique. Rorty opposes both interpretations and suggests a new one – to interpret Derrida texts from the perspective of Wittgensteinian nominalism. The article concludes, that Nietzschean-Wittgensteinian hypothetical interpretation keeps the closest distance with the project of deconstruction as defined by Derrida himself.
Keywords: Derrida; deconstruction; Habermas; rhetoric and logic; neo-Nietzchean philosophy; Norris; epistemic critique; Rorty; nominalism